DIORAMA ART – A POTENTIAL MEDIUM FOR MUSEUM EDUCATION (Journal of Science and Technology, 2016)
The study recognizes the traditional role diorama plays as an effective medium for museum edu- cation and employed both descriptive and experimental methods to produce a diorama to popu- larize it for the Ghanaian populace. It explored the use of non-traditional modelling material (corn shucks and cobs) in the preparation of diorama. The results of the study indicate that corn shucks and cobs which have less use in our environment as raw materials can be used as model- ling medium to produce sculpture. As such other unconventional materials could be explored for modelling in order to open more avenues to sculptors. Besides, diorama could be a mini- museum, a potent tool to keep proper records, document valuable cultural and historic informa- tion to inspire and educate the public; as well as a way of building museums on school campuses to expand classroom teaching and learning.